Handbook of Mechanics of Materials - Schmauder, Siegfried; Chen, Chuin-Shan; Chawla, Krishan K.; Chawla, Nikhilesh; Chen, Weiqiu; Kagawa, Yutaka (Springer Nature Singapore : Imprint: Springer, 2019)
This book provides a comprehensive reference for the studies of mechanical properties of materials over multiple length and time scales. The topics include nanomechanics, micromechanics, continuum mechanics, mechanical property measurements, and materials design. The handbook employs a consistent and systematic approach offering readers a user friendly reference ideal for frequent consultation. It is appropriate for an audience at of graduate students, faculties, researchers, and professionals in the fields of Materials Science, Mechanical Engineering, Civil Engineering, Engineering Mechanics, and Aerospace Engineering.